2013
DOI: 10.1016/j.polymertesting.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrospun polyamide 6 nanofibres on the mechanical properties of a glass fibre/epoxy composite

Abstract: Recently, several types of nanoparticles are frequently incorporated in reinforced epoxy resin composites. A homogeneous dispersion of these nanoparticles is still a problem.Thermoplastic nanofibrous structures can tackle this dispersion issue. Therefore, this paper investigated the effect of electrospun polyamide 6 nanofibrous structures on the mechanical properties of a glass fibre/epoxy composite. The nanofibres were incorporated in the glass fibre/epoxy composite as stand-alone interlayered structures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…Although Hamer et al report an increase in G Ic , only minor improvements and even decreases on both G Ic and G IIc are reported by Palazetti et al [18,20,21]. De Schoenmaker et al [14] state that G Ic increases slightly upon addition of PA 6 nanofibres in UD laminates. Furthermore, tensile tests on crossply laminates showed that the presence of PA 6 nanofibrous interlayers decreased or even stopped the formation of delaminations between reinforcing plies.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although Hamer et al report an increase in G Ic , only minor improvements and even decreases on both G Ic and G IIc are reported by Palazetti et al [18,20,21]. De Schoenmaker et al [14] state that G Ic increases slightly upon addition of PA 6 nanofibres in UD laminates. Furthermore, tensile tests on crossply laminates showed that the presence of PA 6 nanofibrous interlayers decreased or even stopped the formation of delaminations between reinforcing plies.…”
Section: Introductionmentioning
confidence: 93%
“…Uniform PA nanofibrous veils were produced by electrospinning on an in-house multinozzle system [14]. A linear lateral motion of the electrospinning nozzles perpendicular to the production direction guarantees the uniformity of the nanofibrous veils.…”
Section: Electrospinning Of Polyamide Nanofibrous Veilsmentioning
confidence: 99%
“…Three works in literature have been found dealing with tensile properties of nanomodified GFRP laminates, and they do not show the same agreement registered for carbon fibers. In [50] it is showed that tensile properties of UD GFRP laminates are not affected by the presence of PCL nanofiber; in [30], it is shown that PA6 nanofibers caused an increase of stress at failure of the composite of about 6% and 11% when the nanofibers were added during layup and when directly deposited onto the fabric, respectively. A unique use of Silk has been presented in [69], showing a 5% improved tensile strength.…”
Section: Tensionmentioning
confidence: 99%
“…In particular it has been observed that Poisson's ratio mismatches and edge effects have a significant role on the delamination resistance of composite laminates subjected to static and fatigue tensile loads, and it is the field of action of the nanofibers. In [30] it is suggested that nanofibers prevent or minimize the formation of delamination cracks between two fiber plies, and also demonstrated that the nanofibers facilitate the load transfer from the resin to the glass fibers. They also agree with results showed in [60], on the fact that the nanolayers create a matrix-enriched interlayer, which extensive deformation and slower growth of damage improve the tensile properties of the laminate.…”
Section: Tensionmentioning
confidence: 99%
“…Up to now various kinds of polymeric nanofibers have been introduced by researchers for improving fracture toughness of composite laminates: Nylon 6 [13], Nylon 6,6 [14][15][16][17][18], Phenoxy [19], polyvinylidene difluoride (PVDF) [20][21][22], Polysulfone (PSF) [23], Polycaprolactone (PCL) [24][25]. Except PVDF, most other nanofibers have been investigated from different points of view.…”
Section: Introductionmentioning
confidence: 99%